The Effect of Government Expenditure on Developing Corruption levels in Algeria: An empirical study for the period (2003-2018) - بلعابد أديب; مزهود هاجر (Finance and Business Economies Review, 2020)
Abstract: Public spending in Algeria has increased continuously since the beginning of the third millennium, with the aim of improving the country's economic situation, and the overall indicators of the national economy. but after nearly two decades of adopting an expansionary spending policy, most of the internal and external balance indicators have deteriorated and corruption levels have developed in the country. The aim of this study is to find out whether public spending has a role in the spread of corruption. The study found, using the vector self-regression model (VAR), that capital expenditures contributed to the development of corruption levels, while operating expenses contributed to reducing levels of corruption in Algeria during the period 2003-2018.